Folklore use of Osbeckia species from Munnar hills, Kerala - Bosco Lawarence; K. Murugan (Journal of Traditional and Folk Practices (JTFP), 2017)
The genus Osbeckia of Melastomataceae was named by Carl Linnaeus, for the Swedish explorer and naturalist Pehr Osbeck. Osbeckias are native to Eastern Asia, and found in China, Japan, Malaysia, India, Sri Lanka and Australasia. Most species were documented as herbal remedies for curing many human diseases. In India the genus comprises about 22 species out of which 12 species are reported from Kerala. Most of the species are small shrubs and have gained medicinal status in folklore belief from India, China, and Indonesia. Ethnopharmacologically, the leaves, shoots, barks, seeds, and roots of Melastomataceae members have been used to treat diarrhea, dysentery, hemorrhoids, cuts and wounds, toothache, and stomachache. The coloured floral extracts of various genera also revealed wide pharmacological actions such as anti-nociceptive, anti-inﬂammatory, wound healing, antidiarrhoeal, cytotoxic, and antioxidant activities. Many phytochemical constituents including anthocyanins were isolated and identified from different parts of Melastoma and Memycylon species. Thus, the aim of this survey is to present comprehensive information on ethnomedicinal uses and pharmacological activities of Osbeckia species from Kerala. Floral extracts of most of the Osbeckia species contain substantial levels of phenols and anthocyanin. This data validate the folklore use of various species to cure many human disorders. Future studies are planned to evaluate the biological potentialities in terms of anthocyanin profile using in vitro cultures of the species such as O. aspera and O. reticulata.